EVALUASI KOMPOSIT SERAT BIJI KAPUK RANDU BERPENGUAT EPOXY RESIN UNTUK PRODUK KAMPAS REM PABRIKAN FREE ASBESTOS DENGAN PEMBANDING BRAKE SHOES DAN BRAKE PAD PABRIKAN - Stefanus Prasetyo; Gunawan Dwi Haryadi (JURNAL TEKNIK MESIN, 2015)
Brake is a vehicle component that serves to slow or stop the vehicle comfortably. Composite is a kind of new material engineered consisting of two or more materials where each material properties different from each other both chemical and physical properties and remain separate from each other and the material. The purpose of this study to determine the effect of weight percent of the epoxy resin added to the ash kapok seed as the composite material is applied to the motor vehicle brake shoes in the review of the nature of the wear rate, flexibility, and hardness. The results of testing the hardness of composite brake shoes kapok seed is highest at A1 specimens with epoxy resin composition ratio of 5:3 between gray with epoxy resin, the lowest hardness of the specimen B2 with a ratio 7:3 between gray with epoxy resin. In comparison to the violence smallest specimens contained in the specimen K is equal to 47.01 HV and greatest violence contained in a specimen that is equal to 112.14 HV. Value wear rate is highest in B4 specimens with epoxy resin composition ratio is 7: 3, the lowest wear rate is the specimen A1 with epoxy resin composition ratio is 5:3 ash and epoxy resins. In comparison to the rate of wear of the smallest specimens contained in the specimen A with the wear rate of 2.44 x10-7 mm2 / kg and the highest wear rate on the specimen F with a wear rate by 2.82 x10-7 mm2 / kg. Value flexibility composite brake shoes kapok seed is highest at B3 specimen with a composition ratio of 3:2 between Abu B3 + Epoxy Resin, low flexibility is the specimen without treatment with epoxy resin composition ratio is 3:2. In comparison to the flexibility of the smallest specimens contained in the specimen K with the flexibility of 15.85 N / mm2 and l the highest flexibility in specimen F with the flexibility of 27.48 N / mm2 slightly higher than the specimen A which has the flexibility of 27.24 N/mm2.